The long-term effects of bibliotherapy in depression treatment: Systematic review of randomized clinical trials. (December 2017) - Gualano, M.R.; Bert, F.; Martorana, M.; Voglino, G.; Andriolo, V.; Thomas, R.; Gramaglia, C.; Zeppegno, P.; Siliquini, R.
Abstract: Objective: Literature shows bibliotherapy can be helpful for moderate depression treatment. The aim of this systematic review is to verify the long-term effects of bibliotherapy. Methods: After bibliographic research, we included RCTs articles about bibliotherapy programme treatment of depression published in English language between 1990 and July 2017. All RCTs were assessed with Cochrane's Risk of Bias tool. Results: Ten articles (reporting 8 studies involving 1347 subjects) out of 306 retrieved results were included. All studies analyze the effects of bibliotherapy after follow-up periods ranging from 3 months to 3 years and show quiet good quality in methods and analyses. The treatment was compared to standard treatments or no intervention in all studies. After long-term period follow-ups, six studies, including adults, reported a decrease of depressive symptoms, while four studies including young people did not show significant results. Conclusion: Bibliotherapy appears to be effective in the reduction of adults depressive symptoms in the long-term period, providing an affordable prompt treatment that could reduce further medications. The results of the present review suggest that bibliotherapy could play an important role in the treatment of a serious mental health issue. Further studies should be conducted to strengthen the evidence of bibliotherapy's efficacy. Highlights: Investigate the presence of durable effects of bibliotherapy on depressive symptoms Self-help therapy versus standard guided interventions Differences of treatment effects between adults and younger population Research of affordable and prompt depression therapies